PENALARAN ANALOGIS DAN GENERALISASI: STUDI FENOMENOLOGI DAN PENGEMBANGAN DESAIN DIDAKTIS PADA PEMBELAJARAN MATEMATIKA DI PONDOK PESANTREN - Sendi Ramdhani, - (2021)
This research aims to describe the learning obstacles faced by students on learning mathematics in Pondok Pesantren (Islamic boarding schools) related to analogical reasoning and generalization and produce a didactic design that can minimize learning obstacles related to these two aspects. The research method used is qualitative with Design Didactical Research (DDR) which is based on two paradigms, namely interpretive and critical. The interpretive paradigm is used to deeply understand reality based on phenomenological studies and the critical paradigm is used to develop a didactic design based on critical pedagogy. The research subjects who have been observed learning obstacles were students of class IV-VI TMI (equivalent to class X-XII SMA) and teachers from 4 Pesantren Muadalah, which consisted of 2 Pesantren located in Bandung, 1 Pesantren in Garut, and 1 Pesantren in Kuningan. The research subjects for the implementation of the didactic design were students of class VI TMI (equivalent to class XII SMA) one of Pesantren in Kab. Bandung. Data were collected through tests, interviews, observations, focus group discussions, and documents. The results of this research show that: 1) Students face several obstacles in the process of learning mathematics in pondok pesantren which come from ontogenic, didactic, and epistemological obstacles; 2) The obstacles faced by students in the analogical reasoning began with difficulties in the retrieval process so that the mapping process would not occur from one analog to another and consequently the evaluation process from the analogy results and conclusions did not occur; 3) The obstacle that faced the students in generalizing occurs at the expression of generality stage; 4) The didactic design that has been developed consists of subject matter and learning objectives associated with Islamic knowledge and the daily life of the students and worksheets that are structured to minimize learning obstacles related to analogical reasoning and generalizations; 5) The didactic design on mathematics learning can enhance students' analogical reasoning and generalization skills and minimize learning obstacles associated with these two aspects.